Empowerment of Fish Cultivation Supporting Integrated Agriculture in Youth Group, Langsat Permai Village, Bungaraya District, Siak Regency - Dini, Isna Rahma; Hapsoh; Sukendi; Wawan (Talenta Publisher Universitas Sumatera Utara, 2021)
The construction of canal blocking on canals around community agricultural land in Langsat Permai Village through science and technology activities for Mitra Village in 2017-2019 has provided an increase in agricultural yields for both food crops and horticulture. Furthermore, the construction of canal blocking also has an impact on the use of canals for fish farming. Therefore, the purpose of this service activity is to provide assistance in the cultivation of catfish cages and the manufacture of fish feed based on agricultural raw materials and agricultural waste in karang taruna. The success of catfish growth is strongly influenced by the type and amount of feed given. The more feed that is given, the faster the fish will grow but the higher the production costs. Therefore, alternative feeds are needed to reduce the use of fish pellets by making feed made from agricultural raw materials and agricultural waste. Farmer is carried out both in fish cultivation and in the manufacture of fish feed by agricultural raw materials and agricultural waste. Based on the results, all members of karang taruna have understood about catfish farming activities in cages and making fish feed based on agricultural raw materials and agricultural waste. This shows that integrated agriculture has been formed in Langsat Permai Village.